(3JbjjO Ydi GdefXheI GddGejIs - (3CHh YHO Gddg eMeO Hf CMeO Hf eMeO bjGQgs; (3Ydj Hf bGSe Hf eMeO GdJLjHj GdRbGbs ((3CMeO Hf MHjH Gddg s)
(3ChdgG (B:s
(3GdMeO ddg GdPi dGjfHZi GdMeO EdG dg hHYO ajbhd GdYHO Efg efP hbaJ Ydi bUjOI GdEeGe GdRbGb GdJi ai CMcGe GdbVGA , hCfG GTJgi Gdhbha Ydi TQM dgG ade jJjSQ di Pdc Ke TQYJ ai gPG GdJbjjO s
(3BNQgG (B:s
(3hCeG fUjH ZjQ GdHGFY ef HbjI GdTQcGA , hGdeHjY Ydjge , aef de jYde efge HGdHjY , afUHHg ef GdZdI dg , hef Yde hScJ GfJgi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3ChQGbgG eJbUaI GdCWQGa s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3CUhd Gdabgs